Catastrophic health expenditure in Benin: Extent, drivers, and policy implications - Houeninvo, Hilaire Gbodja (Asian Journal of Economic Modelling, 2023)
Large out-of-pocket spending on medical issues can expose households to catastrophic health expenditure, which can result in poverty. This study aimed to estimate the extent of catastrophic health expenditure among households in Benin and to assess the association between household catastrophic health expenditure and household characteristics. We used the 2017 nationally representative household survey for Benin, the “Analyse Globale de la Vulnérabilité et de la Sécurité Alimentaire,” and a logit model to assess the association between catastrophic health expenditure and demographic and socioeconomic household characteristics. The results suggested that 25.49% of households spent 40% of their resources on healthcare. Moreover, households headed by women, the poorest households, those living in rural areas, those headed by a widow, and households with children and elderly members were identified as vulnerable groups that require protection against catastrophic health expenditure. The policy implication of these results is that healthcare financing strategies in Benin should concentrate on finding ways to reduce both out-of-pocket payments and the probability of catastrophic health expenditure. The health insurance policy that is under development in Benin is an opportunity to protect vulnerable groups.